2021
DOI: 10.1111/desc.13117
|View full text |Cite
|
Sign up to set email alerts
|

Infants recognize words spoken through opaque masks but not through clear masks

Abstract: COVID‐19 has modified numerous aspects of children's social environments. Many children are now spoken to through a mask. There is little empirical evidence attesting to the effects of masked language input on language processing. In addition, not much is known about the effects of clear masks (i.e., transparent face shields) versus opaque masks on language comprehension in children. In the current study, 2‐year‐old infants were tested on their ability to recognize familiar spoken words in three conditions: wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 70 publications
5
35
0
4
Order By: Relevance
“… 22 , 24 Two-year-old children recognize spoken words better through an opaque mask compared with a clear face shield, suggesting verbal communication to infants is not harmed by face masks. 25 We are unaware of published research on the long-term effects, if any, on intermittent masking. For medical care, most children 4 to 10 years of age did not prefer unmasked health care professionals to masked health care professionals and did not fear health care professionals with masks.…”
Section: Discussionmentioning
confidence: 99%
“… 22 , 24 Two-year-old children recognize spoken words better through an opaque mask compared with a clear face shield, suggesting verbal communication to infants is not harmed by face masks. 25 We are unaware of published research on the long-term effects, if any, on intermittent masking. For medical care, most children 4 to 10 years of age did not prefer unmasked health care professionals to masked health care professionals and did not fear health care professionals with masks.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that surgical facemasks (used intensively and worldwide in recent times, due to the COVID pandemics) might negatively affect social processing. Impairment might concern the recognition of face identity [1,2 ], emotion reading [3,4,5,6,7,8 ], trustworthiness judgement [9], face likability and closeness impression [6], as well as speech comprehension [10]. Relatedly, it was shown that face blurring impairs the understanding of emotional signals including body language [11].…”
Section: Introductionmentioning
confidence: 99%
“…Es wurden 13 Publikationen [ 24 36 ], davon eine Längsschnittstudie [ 34 ], 2 Querschnittsstudien [ 29 , 35 ], 2 Mixed-Methods-Studien [ 25 , 27 ], eine unkontrollierte Interventionsstudie [ 24 ], 5 Experimentalstudien [ 26 , 30 32 , 36 ] und 2 Übersichtsarbeiten [ 28 , 33 ], eingeschlossen. Von den Studien, die im Feld durchgeführt wurden, behandelten 3 COVID-19 [ 29 , 34 , 35 ], 2 das schwere akute respiratorische Syndrom (SARS; [ 25 , 27 ]) und eine Influenza [ 24 ].…”
Section: Ergebnisseunclassified
“…In einer Experimentalstudie überprüften Singh et al., ob die Fähigkeit zum Erkennen von Wörtern bei 24 Jungen und Mädchen im Alter von 2 Jahren durch das Tragen von Masken beeinträchtigt wurde [ 30 ]. Dazu wurde den Kindern über einen Computerbildschirm das Gesicht einer Frau präsentiert, das entweder a) unbedeckt war bzw.…”
Section: Ergebnisseunclassified
See 1 more Smart Citation